Golden Mandarin(II)-an intelligent Mandarin dictation machine for Chinese character input with adaptation/learning functions - Lin-Shan Lee; Keh-Jiann Chen; Chiu-Yu Tseng; Renyuan Lyu; Lee-Feng Chien; Hsin-Min Wang; Jia-Lin Shen; Sung-Chien Lin; Yen-Ju Yang; Bo-Ren Bai; Chi-Ping Nee; Chun-Yi Liao; et al. (ISSIPNN '94, 1994 International Symposium on Speech, Image Processing, and Neural Networks : proceedings, 13-16 April 1994, Hong Kong Convention and Exhibition Centre, Hong Kong, 1994)
Golden Mandarin (II) is an intelligent single-chip based real-time Mandarin dictation machine for the Chinese language with a very large vocabulary for the input of unlimited Chinese texts into computers using voice. This dictation machine can be installed on any personal computer, in which only a single chip Motorola DSP 96002D is used, with a preliminary character correct rate around 95% at a speed of 0.6 sec per character. Various adaptation/learning functions have been developed for this machine, including fast adaptation to new speakers, on-line learning the voice characteristics, task domains, word pattern and noise environments of the users, so the machine can be easily personalized for each user. These adaptation/learning functions are the major subjects of the paper.< >